Efeito de diferentes agentes bioativos de origem natural e sintética na estabilidade de união em dentina - Mendes, Talita Arrais Daniel (2022)
The use of polyphenols (PF) as a biomodifying strategy has been quite frequent within Restorative Dentistry, with the purpose of improving the adhesive strategy, reducing degradation mechanisms that occur in the hybrid layer. Therefore, the objective of the present thesis is to evaluate the effect of different bioactive agents of natural and synthetic origin on the bond stability of restorations with composite resin in dentin. This study consists of three chapters, where the first chapter aimed to evaluate, through a systematic review and metaanalysis, the effect of grape seed extract (GSE) on the stability of restorations with composite resin in dentin. A search was carried out in 4 databases: Online System of Literature Search and Analysis, Web of Science, Science Direct and Scopus. The following descriptors were used: Proanthocyanidins, Cross-Linking Reagents and Dentin with their respective entry terms. A total of 1074 articles were found and, after applying the PRISMA flowchart checklist, nine articles were selected. It can be concluded that ESU, used as a pre-treatment, improves the bond stability of adhesive systems to dentin in in vitro studies. The second chapter aimed to analyze the biomodifying effect of galloylated esters of natural origin on dentinal collagen. For this purpose, the following biomodification agents were used as dentin pretreatment: epigallocatechin-3-gallate 0.1% (EGCG), tannic acid 1% (TA), proanthocyanidin 6.5% (PAC) and distilled water (DW) as a negative control. The dependent variables of the study were the modulus of elasticity (ME), quantitatively evaluated through the 3-point bending test (n=15), mass change (n=15), on an analytical precision balance and bond strength to dentin (n=8), (µTSB), performed by a universal mechanical testing machine. A qualitative analysis of collagen was also performed using Fourier transform infrared spectroscopy (FT-IR) (n=3) and micropermeability test (n=3) of the dentin/resin bonding interface. It was noted that AT significantly increased collagen ME. PAC and AT are able to maintain the stability of bonding the resin to dentin after 6 months. However, it was concluded that the presence of galoil groups in natural polyphenols does not seem to improve the bonding stability of a dentin restoration. The objective of the third chapter was to verify the use of propyl gallate as a biomodifying agent of dentin collagen in the dentin bonding process. The following substances were used as dentin pretreatment: 0,1% propyl gallate (PGa0.1%); 1% propyl gallate (PGa1%); 10% propyl gallate (PGa10%); 5% glutaraldehyde (GA5%); and distilled water (DW). The dentin treated by the different pre-treatment solutions was analyzed by means of FT-IR (n=3), as well as the bond strength of an adhesive system for conditioning and washing dentin (n=8), with 24 hours and 6 months of aging. PGa, at different concentrations, was able to perform chemical bonds with demineralized dentin. PGa10% was able to generate an increase in the bond strength of dentin to resin in an immediate analysis, but after 6 months there was a decrease in it. The GA5%, PGa0,1% and PGa1% groups were able to maintain this stability. Therefore, the search for natural and synthetic polyphenols that have a high bioactive capacity, such as galloylated esters, has been promising; however, despite the more pronounced chemical interaction with dentinal collagen, in general, these compounds do not play an efficient role in maintaining the stability of these bonds over time.